Judicial discretion and contempt power: two elements of equity that would benefit the EAPO and future EU-wide provisional and protective measures - Kyriakides, N (2016)
A person filing a civil claim faces the risk of being unable to enforce a favourable judgment. This is because their opponent may dissipate his assets and consequently be unable to satisfy a judgment given against him. Several mechanisms seek to alleviate this risk by preserving the defendant’s assets pending judgment. These are predominantly the civilian in rem order and the common law freezing order. Fundamental differences between the common and civil law traditions may be observed in the freezing order and its civilian counterpart. Primarily, these are to be found in the margin of discretion given to the judge and the sanctions against non-compliance. The latter issue is closely related to the entity against which an order is directed: in the common law it is directed against the person, while in the civil law, against the asset. The significantly diverse approaches in these areas show the different course each of the legal families has taken in the administration of justice. The problem of preserving assets pending judgment becomes more complicated when the assets are not located in the same country as the courts with jurisdiction on the merits. The recently introduced European Account Preservation Order (‘EAPO’) regulation is a pre-judgment instrument which enables a litigant to obtain an order preventing the transfer of funds held by the respondent in a bank account within the EU. It is the first of what may become several EU-wide provisional and protective measures. At first glance, the EAPO resembles the continental model rather than its common law counterpart, and, thus, brings into the open the differences between the two traditions in the area of provisional and protective measures. This work examines whether the features of the common law tradition—which in fact derive from the law of equity—ie judicial discretion in granting or refusing relief and contempt of court sanctions, could improve the EAPO as well as other EU-wide provisional and protective measures that may follow. It is argued that greater judicial discretion and a contempt sanction, provided that they are kept within certain limits, would improve the EAPO and similar measures in terms of efficiency and fairness.